Fan films: da produção caseira a um cinema especializado - Curi, Pedro Peixoto (2010)
With rapid technological development, easier access to cheaper equipments - such as new digital camcorders - and the variety of new possibilities in production and exhibition, fans have been able to trespass the limits of their imagination from paper to more sophisticated formats. Fans that are not able to find in the official market what they desire, now have the capability of producing the movies and stories they would like to see, using notorious stories and characters and making them available on the Internet for others. Fan films can be considered the most complex products of fan culture, a place of development of tendencies, talents and professionals. This kind of production also helps to analize fandom and its relations. Slowly, fan films are finding their space and reaching bigger audiences. This dissertation analizes what has made the fan films possible, the specificities of this new audiovisual production that leads to an specialized cinema, some titles produced over the world and the impact on the movie industry and the cinema studies